Macroeconomic Determinants of Auto Sales in ASEAN: An Empirical Study in Five Major ASEAN Countries - Suwinto Johan (JAS (Journal of ASEAN Studies), 2020)
This research examines the determinants of car sales in ASEAN countries. The research concentrates on five macroeconomic variables (consumer price index, gross domestic product (GDP) per capita, changes in gross domestic product per capita, foreign exchange rate, and interest rate). The total sample is 12 years of automobile sales in five ASEAN countries from 2005 – 2016. The five ASEAN countries are Indonesia, Thailand, Malaysia, Singapore, and Vietnam. This paper used the multilinear regression method with Statistical Package for the Social Sciences (SPSS) software to test the research model. For interest-rate variables, we used a lag of one year. The empirical results show that the previous period for inflation, gross domestic product per capita, interest rate, and the foreign exchange rate significantly influenced on car sales in five ASEAN countries. The growth of GDP per capita does not influence car sales.